Enhancing the Quality of Islamic Education in Madrasah Aliyah in Indonesia: The Integral Role of Leadership and Quality Management - Famelia Widyarini Soetrisno; Moh. Ali (Bulletin of Indonesian Islamic Studies, 2025)
Improving the quality of education in madrassas is very important in responding to contemporary challenges and national education policies. This study aims to analyze the role of madrasah principal leaders in transforming the quality of education in Madrasah Aliyah Negeri Tegal City. Using a systematic review approach, this study synthesizes academic literature and empirical findings, combined with field observations and in-depth interviews. The results of the study show that madrasah leadership significantly affects the planning, organization, implementation, and evaluation of the quality of education. Supporting factors such as leadership commitment and policies enable accelerating quality transformation, while challenges such as resource constraints and resistance to change serve as major barriers. The strategies implemented include a participatory approach, ongoing training, and effective communication with stakeholders. This study contributes to the development of transformative leadership models based on Islamic values and sustainable quality management in madrasah environments. These findings conclude that madrasah principals act as agents of change who are able to navigate organizational challenges through visionary and collaborative leadership.